The opt-out revolution: A descriptive analysis - Heather Antecol (Institute for the Study of Labor (IZA), 2010)
Using data from the 1980, 1990, and 2000 US Census, I find little support for the opt-out revolution - highly educated women, relative to their less educated counterparts, are exiting the labor force to care for their families at higher rates today than in earlier time periods - if one focuses solely on the decision to work a positive number of hours irrespective of marital status or race. If one, however, focuses on both the decision to work a positive number of hours as well as the decision to adjust annual hours of work (conditional on working), I find some evidence of the opt-out revolution, particularly among white college educated married women in male dominated occupations.
urn:nbn:de:101:1-201008116007
Keywords: J13; J15; J16; J22; 330; opting out; female labor supply; extensive/intensive margin; race/ethnicity